Covalent organic framework with Cu-containing compounds for enhancing flame retardancy and smoke suppression effects on epoxy resin. (May 2022) - Cui, Mulan; Mu, Xiaowei; Cai, Wei; Wang, Xuan; Ye, Daolin; Xi, Jianchao; Hu, Yuan; Xing, Weiyi
Graphical abstract: Highlights: COFs@CuO, COFs@Cu2 O, COFs@Cu(OH)2 with good smoke suppression effect are prepared. EP composite exhibits good flame retardancy, smoke suppression and mechanical performance. The flame retardant mechanism of EP and its nanocomposite is revealed. Abstract: To enhance the flame retardancy and smoke suppression effects of epoxy resin (EP), three inorganic compounds of copper modified covalent organic frameworks (COFs), COFs@CuO, COFs@Cu2 O, COFs@Cu(OH)2 are synthesized. The flame retardancy of EP can be significantly uprated by adding only 2 wt% COFs@Cu2 O. The PHRR and THR yield of EP/COFs@Cu2 O decrease by 36.6% and 20.4% compared with that of unmixed EP, respectively. The smoke density of EP/COFs@CuO reduces by 54.3% compared with that of pure epoxy. Moreover, the peak CO yield (COPR) of EP/COFs@Cu2 O nanocomposites is 42.8% lower than that of unmixed EP. In addition, the impulse strength of EP/COFs@CuO augment 50.7% than that of pure epoxy, and the tensile strength of EP/COFs@CuO is 80.0% higher than that of EP/COFs. The synergy between metallic inorganic compounds and COFs is investigated. This work proves a guidance for preparation of high safety EP.